Emotion decides and reason justifies (Journal of Parents and Teachers, 2014)
Until very recently, the intelligence was considered innate and unchangeable. Gardner defines intelligence as an ability. The ability or inability is not so much a concept itself. Gardner developed a good rating for distribution to the population, without having to be labeled inferior or superior, but does not satisfy the urgent human need to get out of their specific capacity and transfer this skill to other areas to master other territories for which it has no such bias in the early stages of learning. With the model we Conscious Emotional Bonding out of this circumstance.
Keywords: Multiple Intelligences; Emotional Bonding Conscious; emotion; learning.